1997
DOI: 10.1590/s0100-879x1997000300002
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of anxiety: an ethological perspective

Abstract: In the field of anxiety research, animal models are used as screening tools in the search for compounds with therapeutic potential and as simulations for research on mechanisms underlying emotional behaviour. However, a solely pharmacological approach to the validation of such tests has resulted in distinct problems with their applicability to systems other than those involving the benzodiazepine/GABA A receptor complex. In this context, recent developments in our understanding of mammalian defensive behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
244
1
27

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 538 publications
(299 citation statements)
references
References 94 publications
15
244
1
27
Order By: Relevance
“…risk assessment, head-dipping) together with conventional spatiotemporal measures of open-arm avoidance. Studies using this modified version of the plus-maze showed that risk assessment measures are generally more sensitive to drug effects than are avoidance measures [73]. For example, comparison between BZ and 5-HT 1A anxiolytics revealed differences in anxiolyticlike profiles that may not be detected by conventional scoring.…”
Section: Mouse Models Of 'Normal' or 'State' Anxietymentioning
confidence: 99%
See 3 more Smart Citations
“…risk assessment, head-dipping) together with conventional spatiotemporal measures of open-arm avoidance. Studies using this modified version of the plus-maze showed that risk assessment measures are generally more sensitive to drug effects than are avoidance measures [73]. For example, comparison between BZ and 5-HT 1A anxiolytics revealed differences in anxiolyticlike profiles that may not be detected by conventional scoring.…”
Section: Mouse Models Of 'Normal' or 'State' Anxietymentioning
confidence: 99%
“…Over the past three decades, a bewildering diversity of tests has been developed which claim face, construct and/or predictive validity as animal models of anxiety disorders (for review, see [73,89]). While most of these procedures use rats as subjects, a few of them have been validated with mice.…”
Section: Mouse Models Of Anxietymentioning
confidence: 99%
See 2 more Smart Citations
“…Por outro lado, sabe-se que ratos têm predileção por explorar espaços fechados em comparação aos abertos e quando numa situação de escolha como, por exemplo, num labirinto em Y, preferem consistentemente os braços fechados (Ramos et al, 1997;Rodgers e Johnson, 1995, Rodgers et al, 1997. utilizou-se arena circular, circundada com parede de madeira (Chieffi et al, 2010); o piso do aparato era dividido em 46 partes, por meio de círculos e segmentos radiais.…”
Section: Diversos Autores Observaram Em Camundongos Infectados Com Tunclassified